2018
DOI: 10.1136/bcr-2017-221831
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniaeinfection presenting as stroke and meningoencephalitis with aortic and subclavian aneurysms without pulmonary involvement

Abstract: A 39-year-old Philipino man presented with acute onset fever and headache. Neurological examination was normal except for neck stiffness. There was no history of chest pain, cough or breathlessness. Cerebrospinal fluid (CSF) showed a mild increase in protein with normal sugar and lymphocytic pleocytosis. CSF PCR for herpes simplex and varicella zoster virus was negative. He developed acute right haemiplegia a week after hospitalisation. MRI showed acute infarct in the left centrum semiovale. His angiogram show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It has been speculated that M pneumoniae may disrupt the integrity of the vascular endothelium and upset the equilibrium between coagulation and anticoagulation by eliciting an inflammatory response, which may lead to hypercoagulation and thrombosis. [ 11 , 12 ] A direct invasion mechanism has been proposed in patients with stroke because M pneumoniae DNA was detected in cerebrospinal fluid. [ 13 ] Gu et al [ 14 ] reported a series of pediatric cases of M pneumoniae pneumonia, including 1 case complicated with occlusion of the right MCA and cerebral infarction and 1 case with occlusion of the basilar artery and posterior cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that M pneumoniae may disrupt the integrity of the vascular endothelium and upset the equilibrium between coagulation and anticoagulation by eliciting an inflammatory response, which may lead to hypercoagulation and thrombosis. [ 11 , 12 ] A direct invasion mechanism has been proposed in patients with stroke because M pneumoniae DNA was detected in cerebrospinal fluid. [ 13 ] Gu et al [ 14 ] reported a series of pediatric cases of M pneumoniae pneumonia, including 1 case complicated with occlusion of the right MCA and cerebral infarction and 1 case with occlusion of the basilar artery and posterior cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Mycoplasma pneumoniae infection may present with thrombus in almost any part of the body (Tables I-VI) Thrombosis caused by Mycoplasma pneumoniae infection was most reported in the head and neck, followed by in the limbs. Certain patients with normal chest radiography and Mycoplasma pneumoniae infection also developed thrombi (28,33,34). Certain patients developed thrombi in only one part of the body, while others developed thrombi in multiple parts.…”
Section: Location Of Thrombosismentioning
confidence: 99%
“…Cerebral infarction developed 2 days to 3 weeks after Mycoplasma pneumoniae infection (29)(30)(31)(33)(34)(35)(36)(37)(38)(39)(40)(41)43,44). Chest imaging of certain patients revealed pulmonary embolism 11-29 days after Mycoplasma pneumonia infection (52).…”
Section: Thrombosis Onset Time From Mycoplasma Pneumoniae Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it may cause serious complications in some children in addition to the respiratory symptoms. There are growing reports of venous thrombosis or arterial embolism as the result of a MP infection [7][8][9][10] . MP infection can lead to hypercoagulable state, vascular endothelial damage, and even compromise the hepatic function affecting the synthesis of coagulation factors and thrombin.…”
Section: Introductionmentioning
confidence: 99%